Medidas de condutividade na caracterização de complexos inorgânicos: um levantamento bibliográfico - Velho, Rodrigo Garcia (2006)
In this work was done a review of the data published in inorganic chemistry journals (Inorganic Chemistry and Inorganica Chimica Acta in the years 1973-2005 and 1983-2005, respectively) on values of measurements of conductivity of coordination compounds in organic solvents and water. The main objective of the work was up to date the data collect by GEARY in his paper The use of conductivity measurements in organic solvents for the characterization of coordination compounds published in the journal in 1971 . The data of the conductivity of the complexes were listed o a table according to the solvent used for the measurements in the respective electrolyte and the final propose of the work was to establish a range of conductivity for each type of electrolyte.